(untitled) (REVISTA NODO, 2019)
The training of construction workers, professionals and the community in general in alternative and traditional construction technologies such as the one that uses land, in its different techniques, through methodologies that share knowledge horizontally as “learning by doing”, responds to the problem urgent to train capable technicians in the conservation of the built heritage, to the need to recover and give continuity to traditional and tested construction systems, which allow to address the housing deficit and the construction of a sustainable habitat.